Implementasi Akad Syirkah Dalam Ekonomi Islam (Studi Kasus Usaha Peternakan Ayam Boiler Pola kemitraan Di Kecamatan Silinda) - Elizar Sinambela; Rafika Chudriana putri; Basmaida Waty Tambusay; Muhammad Yusuf; Isnaini Harahap (Ekonomikawan: Jurnal Ilmu Ekonomi dan Studi Pembangunan, 2023)
Currently, many business activities are carried out by way of cooperation. One of the forms of cooperation in Islam is called the Syirkah Akad, which is a cooperation agreement by combining the resources owned for the achievement of common goals. This research was conducted with the aim of knowing the implementation of the Syirkah Contract in society, especially in the case of the Partnership Pattern Boiler Chicken Farming Business in Silinda District. The method used is field research with an Islamic law research approach. The results obtained from this study are that the Partnership Pattern Boiler Chicken Farming in the Silinda sub-district is a collaborative activity using the Syirkah Inan Contract. Where both parties agree to cooperate in terms of work (charity) and capital (mall). In its implementation, Inan's syirkah contract was carried out in accordance with the pillars of the Syirkah contract, namely the existence of consent and qabul, the subject of the agreement and the object of the contract which includes capital, work, profits and losses. In the perspective of Islamic microeconomics, the implementation of the Syirkah Contract that occurred in this case, has been able to explain how demand by consumers (PT. Karya Energi Mandiri) and offers made by producers (breeders), as well as the behavior of consumers and producers who are bound by the syirkah so as to be able to make an economic decision regarding pricing, costs and markets based on sharia provisions.